E-Commerce Shopping Intentions in the Industrial 4.0 Era: An Analysis of the Impact of Millennium Attitudes - Lokunuha, Denta Sella (Ridwan Institute, 2023)
The rise of the millennial generation defined the fourth industrial revolution. This generation is known as a generation that is innovative, creative and likes freedom. The contemporary generation, often known as the millennial generation or the generation that was born at the turn of the millennium, is currently exhibiting highly noticeable shifts in consumer lifestyles. Digital technology is simultaneously beginning to permeate many facets of life in this time period.This study uses quantitative data. The sample used in this study was 300 millennial generation respondents at a private university in Surabaya. The results: trust, price and service quality have a significant effect on the online buying attitude of the millennial generation, subjective norms have an effect on the online buying interest of the millennial generation and attitudes have a significant effect on the online buying interest.